Agro-waste–based porous hydroxyapatite: microstructural evolution and mechanical performance - Dele-Afolabi, T. T.; Azmah Hanim, M. A.; Adeleke, A. O.; Kandasamy, M.; Sirajudeen, Abdul Azeez Olayiwola; Ogunrinde, Samuel Oluwaseun (John Wiley and Sons, 2026)
Bone tissue engineering remains a promising method for bone replacement or augmentation,even though the design of high-performance scaffolds still poses a significant challenge. This study evaluated the fabrication of porous hydroxyapatite bioceramics with rice husk and corn cob as space holders. The X-ray diffractometer (XRD) data demonstrated that after the decomposition of the starting rice husk space holder, silica was retained as rice husk ash in the porous hydroxyapatite. According to empirical findings, the porosity (8.97%–41.89%) and average pore size (36.48–74.02 μm) of porous hydroxyapatite continued to be linearly correlated with the space-holder loading. The developed porous HAp bioceramics exhibited tensile strength, flexural strength, and hardness values of 12.62–2.85 MPa, 37.38–9.4 MPa, and 223.7–60.9 HV, respectively, indicating an overall inverse relationship between the mechanical properties and porosity. Furthermore, the silica peak shown in the XRD pattern of the RH-shaped porous HAp is the key distinguishing feature, favoring their comparatively higher strength, especially at higher space-holder loading. The porous hydroxyapatite developed using different agricultural waste space holders exhibits adequate porosity and robust mechanical properties, highlighting its potential as a promising bone replacement material for tissue engineering applications.